Preparation of high-purity molybdenum oxide by oxidative roasting of molybdenum concentrate pellets: Optimization of pelletization performance - Yanrui Hou; Ruoyu Yang; Jun Luo; Hu Sun; Guanghui Li; Tao Jiang (Journal of Materials Research and Technology)
The synchronous oxidation-volatilization process of molybdenum concentrate pellets addresses several key challenges in traditional pyrometallurgy, such as low volatilization rates due to sintering and reduced product purity caused by severe dust pollution during direct ore powder smelting. Efficient pelletization of molybdenum concentrate is essential for advancing its industrial application. However, molybdenite-a typical sulfide mineral-exhibits strong hydrophobicity, which significantly hinders pellet formation and fails to meet industrial standards. To overcome this, the present study introduces kaolin into the pelletization system as a natural binder with excellent hydrophilicity, effectively improving the surface wettability of molybdenite and enabling the development of a high-efficiency composite pelletization technology. The optimized pellets demonstrate excellent physical properties, including a compressive strength of 18.12 N, an abrasion index of 0.34, and a porosity of 25.52 %, along with good structural integrity and gas permeability required for oxidative roasting. Under industrially relevant conditions, the pellets exhibit outstanding roasting performance, achieving a high molybdenum volatilization rate of 91.61 %. Post-roasting, high-purity MoO3 crystals (99.99 %) are obtained without the need for secondary purification, confirming the process's effectiveness in impurity control and stable production of high-quality products.